Активные компоненты оптических систем со спектральным уплотнением каналов - Фролов, А. В.; Иванцова, А. А. (Харьковский национальный университет радиоэлектроники, 2015)
The spectrum of the signal modulated in intensity spectrum resembles amplitude modulated signal. It comprises side components and the spectrum of the original signal should be limited to the first harmonic of the clock frequency. Frequency stability for STM- 64 will be sanctioned in the neighboring frequency channel group, unacceptable increase in noise suppression and signal the failure of the system.
Keywords: система передачи сигналов; оптические усилители; оптические системы; спектральное уплотнение каналов